Development and usability of a gamified app to help children manage stress: an evaluation study. - Iolie Nicolaidou; Tozzi, Federica; Kindynis, Philippos; Panayiotou, Marinos; Antoniades, Athos (My University, 2019)
Children generally have difficulty managing stress. As a result, stress may escalate to anxiety. Informal-learning, stress prevention interventions that are easily accessible on mobile devices could be one way for children to learn how to manage stress before it reaches the levels of anxiety. There are less than a handful of stress management apps targeting children presently available and these do not combine gamification techniques with behavior change theory. This study describes the design and development of a gamified interactive storytelling mobile app to teach young children how to manage stress through relaxation exercises. It evaluates the app’s usability using learning analytics data and the SUS usability scale. The gamified app called Kids’ Stress Relief received a satisfactory usability score (73.55) and was well accepted by a sample of 71 children (5-12 years old). It may have the potential to support children in learning how to perform stress relief techniques as a stand-alone application. Instructional and design implications, of interest to developers of psychology-based apps, are drawn.
Keywords: emerging technologies; games for learning